2014
DOI: 10.1016/j.meegid.2014.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Epistatic selection and coadaptation in the Prf resistance complex of wild tomato

Abstract: Natural selection imposed by pathogens is a strong and pervasive evolutionary force structuring genetic diversity within their hosts' genomes and populations. As a model system for understanding the genomic impact of host-parasite coevolution, we have been studying the evolutionary dynamics of disease resistance genes in wild relatives of the cultivated tomato species. In this study, we investigated the sequence variation and evolutionary history of three linked genes involved in pathogen resistance in populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…R genes have to be prolonged by studying the complex of resistance of the evolution of R gene. Grzeskowiak et al (2014) studied the mechanism of resistance in tomato focusing on Pto/Fen/Prf resistance complex. Some studies have shown that studying non-host resistance (NHR) may lead to and devise mechanisms of resistance that are long lasting and independent of recognition of R protein.…”
Section: Future Prospects Of Applying Molecular Techniques In Plant Dmentioning
confidence: 99%
“…R genes have to be prolonged by studying the complex of resistance of the evolution of R gene. Grzeskowiak et al (2014) studied the mechanism of resistance in tomato focusing on Pto/Fen/Prf resistance complex. Some studies have shown that studying non-host resistance (NHR) may lead to and devise mechanisms of resistance that are long lasting and independent of recognition of R protein.…”
Section: Future Prospects Of Applying Molecular Techniques In Plant Dmentioning
confidence: 99%
“…One way to tackle the durability issue of R genes is to study R gene evolution in the context of the whole resistance complex. Well-studied resistance mechanisms in tomato allowed this issue to be elegantly addressed by Grzeskowiak et al (2014) for the Pto/Fen/Prf resistance complex. Pto homologs and Prf are co-localized genomically, suggesting that they evolved concurrently.…”
Section: Breeding For Resistance: Strategies Deployed So Farmentioning
confidence: 99%